2019
DOI: 10.1002/jcsm.12413
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrate intake is associated with muscle function in older women

Abstract: Background In younger individuals, dietary nitrate supplementation has been shown to improve short‐term vascular and muscle function. The role of higher habitual nitrate intake as part of a typical diet on muscle function in ageing has not been investigated. A cross‐sectional study of relationships between dietary nitrate and measures of muscle function in older community‐dwelling Australian women ( n = 1420, ≥70 years) was undertaken. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 42 publications
1
57
0
Order By: Relevance
“…For healthy older populations, studies found that fish oil‐derived omega‐3 PUFA intake, high protein intake, resistance exercise training, and vitamin D3 supplements can be helpful for improving muscle mass and functions as well as preventing sarcopenia 61‐65 . Nitrate‐rich diets and oral nutritional support combined with exercise were also associated with better muscle functions 66,67 . Moreover, beta‐Hydroxy‐beta‐methylbutyrate supplements, high‐intensity resistance training, and dairy protein intake could be useful therapies for improving sarcopenia, and fat and fish dietary pattern might be associated with lower risk of sarcopenia in patients with GI cancer 68‐71 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For healthy older populations, studies found that fish oil‐derived omega‐3 PUFA intake, high protein intake, resistance exercise training, and vitamin D3 supplements can be helpful for improving muscle mass and functions as well as preventing sarcopenia 61‐65 . Nitrate‐rich diets and oral nutritional support combined with exercise were also associated with better muscle functions 66,67 . Moreover, beta‐Hydroxy‐beta‐methylbutyrate supplements, high‐intensity resistance training, and dairy protein intake could be useful therapies for improving sarcopenia, and fat and fish dietary pattern might be associated with lower risk of sarcopenia in patients with GI cancer 68‐71 .…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63][64][65] Nitrate-rich diets and oral nutritional support combined with exercise were also associated with better muscle functions. 66,67 Moreover, beta-Hydroxy-beta-methylbutyrate supplements, high-intensity resistance training, and dairy protein intake could be useful therapies for improving sarcopenia, and fat and fish dietary pattern might be associated with lower risk of sarcopenia in patients with GI cancer. [68][69][70][71] Although drug therapies such as testosterone, myostatin antibodies, and activin receptor antibodies might have potential effects on sarcopenia treatment, 72 and recently a randomized controlled study reported that treatment with bimagrumab over 16 weeks increased muscle mass and strength in older adults with sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…We selected articles investigating nutrition interventions, macronutrient intake below recommended, and micronutrient deficiency. We found 26 articles: 10 clinical trials, 3,25–33 five cross‐sectional studies, 34–38 three experimental animal studies 39–41 (one of which also included a human cross‐sectional analysis 38 ), three narrative reviews, 6,42,43 two retrospective studies, 44,45 two systematic reviews or meta‐analyses, 46,47 and one questionnaire survey 48 . Within the 320 original and review articles published in 2018, 2019, and 2020 in JCSM , the 26 articles on nutrition that we found comprise approximately 8%.…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 92%
“…Seven studies 25,27–30,32,33 investigated the effects of multimodal interventions (defined as two or more approaches) on muscle mass. Articles also explored the associations of protein intake, 46,47 iron deficiency, 37,42 micronutrients, 35 calorie restriction, 43 nitrate dietary intake, 36 retrospective evaluation of early dietary supplementation, 44 and overall dietary intake and patterns 34 with several clinical outcomes and/or biomarkers of sarcopenia or cachexia. Two studies evaluated the perceptions of oncology patients regarding disease‐related nutritional issues and barriers to effective nutritional interventions 45,48 .…”
Section: Taking a Stand: Journal Of Cachexia Sarcopenia And Muscle Nmentioning
confidence: 99%
“… Liu et al [ 108 ] 2900 Prospective (Blue Mountains Eye Study) 15 FFQ CVD mortality In multivariable-adjusted analysis, participants in quartile 4 [> 137.8 mg/d; HR 0.63 (95% CI 0.41, 0.95)] of vegetable NO 3 − intake had lower hazards for CVD mortality compared to participants in quartile 1 (< 69.5 mg/d) Mendy et al [ 109 ] 17,618 Prospective (NHANES) 4.3 Urinary NO 3 − in spot urine samples Hypertension and CVD prevalence and all-cause mortality 1-unit increase in log-transformed urinary NO 3 − was associated with a > 30% decrease in the odds of hypertension (odds ratio, 0.67; 95% confidence interval [CI], 0.55–0.81), stroke (OR, 0.61, 95% CI, 0.43–0.87) and cardiovascular mortality (HR, 0.44; 95% CI, 0.26–0.73) Jackson et al [ 110 ] 5324 Prospective (Australian Longitudinal Study on Women’s Health) 15 FFQ Incidence of self-reported CVD-related complications Women reporting higher total dietary NO 3 − intakes (Q4 > 78.2 mg/d) and vegetable NO 3 − intakes (Q4 > 64.4 mg/d) were 25 and 27% reduced risk of developing CVD-related complications, respectively. Jackson et al [ 111 ] Nurses’ Health Study and Health (62,535 women) Prospective 26 FFQ Coronary heart disease Dietary NO 3 − intake was not related to risk of CHD after adjustment for other lifestyle and non-vegetable dietary factors Sim et al [ 112 ] 1420 Cross-sectional (Perth Longitudinal Study of Aging in Women) FFQ Hand-grip strength and time up and go (TUG) Higher NO 3 − intake (31.2 mg/d) was associated with lower odds for weak grip strength (OR 0.84, 95% CI 0.74–0.95, P = 0.005) and slow TUG (OR 0.86, 95% CI 0.76–0.98, P = 0.021) Riddell et al [ 113 ] 2656 Prospective 1.5 Urinary NO 3 − to creatinine ratio (uNCR) Prediction of renal transplant rejection Overall uNCR was h...…”
Section: Main Textmentioning
confidence: 99%